Using vitreous humour and cerebrospinal fluid electrolytes in estimating post-mortem interval - an exploratory study. Issue 6 (1st November 2020) - Garland, Jack; Olds, Kelly; Rousseau, Guillaume; Palmiere, Cristian; Ondruschka, Benjamin; Kesha, K.; Glenn, Charley; Morrow, P.; Stables, S.; Tse, R.
ABSTRACT: Many previous studies have investigated the use of post-mortem biochemistry to estimate the post-mortem interval (PMI). Vitreous humour (VH) potassium and sodium/chloride levels are well recognized to increase and decrease, respectively, in the post-mortem period but have limited ability in estimating PMI. Cerebrospinal fluid (CSF) is described to have different post-mortem biochemical properties than VH, but is not well studied in relation to estimating PMI. This exploratory study examined 20 paired cases of VH and CSF to investigate their use in estimating PMI. Linear univariate analysis showed Na +, Cl − and K + in VH and CSF share similar trends, but only K + in VH and CSF collected via lumbar puncture (LP) showed a significant regression coefficient (p < 0.01). In subsequent linear multivariate analysis, the coefficient for K + in VH remained positive and significant but not for K + in CSF. Only minor improvement was observed in the multivariate analysis. Our study showed changes in analytes in VH and CSF follow similar trends. K + in VH is most accurate in estimating the PMI, with no significant improvement in accuracy when K + in CSF is combined. Thus, the role of CSF electrolytes in estimating PMI may be very limited.